Measurement of Human Blood pressure a guideline for General Practitioners (University Heart Journal, 2009)
Blood pressure is a vital parameter. Stephen Hales first measured BP and Scipione Riva-Rocci developed the prototype of the present day sphygmomanometer. Both directly and indirectly BP can be measured. The indirect method Includes sphygmomanometric method, ultrasound doppler method, oscillometric method, self measurement and ambulatory BP monitoring. For proper measurement of BP by auscultatory method, one should have adequate knowledge of equipment and cuff size, proper technique and Korotkoff sounds. In different situations like arrhythmias, shock, hyperkinetic circulatory states and aortic regurgitation, BP should be measured carefully. In recent years home BP monitoring and ambulatory BP monitoring are becoming popular. Care must be taken to avoid both underestimation and overestimation of BP recording.   doi: 10.3329/uhj.v5i1.3438 University Heart Journal Vol. 5, No. 1, January 2009 28-31